Ideological Extremism Among Syrian Refugees Is Negatively Related to Intentions to Migrate to the West. (September 2021) - Jasko, Katarzyna; Webber, David; Molinario, Erica; Kruglanski, Arie W.; Touchton-Leonard, Katharine
The conflict in Syria created a dire humanitarian situation, as nations around the world struggled with how best to deal with the more than 6.6 million Syrian refugees who fled their homes to escape aggression. Resistance to granting refugee status to individuals often originates in the belief that the influx of refugees endangers national security because of the presumably extremist religious and political beliefs that refugees hold. The present research surveyed Syrian refugees residing in Jordan, Lebanon, Turkey, and Iraq ( N = 1, 000). The results revealed that the majority of surveyed refugees did not intend to migrate to the West and would rather return to their home country. More importantly, refugees most interested in moving to Western countries were the least likely to subscribe to Islamist extremism or to harbor negative sentiment toward the West. Theoretical and practical implications for addressing the current refugee crisis are discussed.